Conducting a Mini Needs Assessment-Instructional Systems Development - Consultant, Kavita (Association for Talent Development, 1995)
This issue defines a mini needs assessment as a process for identifying problems and solutions in a condensed period of time. It outlines a process model and guidelines for implementing the model and offers a mini need assessment stakeholders interview guide and sample action plan.